PENILAIAN KINERJA KARYAWAN PT PEGADAIAN (PERSERO) : PENDEKATAN MULTISUMBER - Suhernawati Suhernawati (Universitas Pendidikan Nasional, 2014)
Performance appraisals conducted in this study using the method of performanceassessment from various sources, namely from the immediate supervisor, supervisor indirectly,the employees themselves, co-workers and customers.The purpose of this study was to determine the objective performance assessment PTPegadaian (Persero) from various sources. The method used in this study the quantitativedescriptive. Population data retrieval techniques. Methods of data collection usingquestionnaires filled out by all employees and customers.Based on the results of this case study is evidenced by the results of a questionnairedistributed to the immediate supervisor, indirect supervisor, the employee and the consumer,showed no difference between the perceptions of performance appraisal immediate supervisor,supervisor indirectly, yourself, co-workers and customers. All aspects of perception increasedsignificantly. Aspects of the self are aspects that contribute the greatest aspects of assessmentand immediate superior in the assessment gives the smallest donationKeywords: Performance Appraisal, Performance Appraisal Method Multi - source